The role of internet integration in relation to farmers’ income and perceived social fairness - Ke Zheng; Yanan Feng; Ruyu Zhang; Yufeng Li; Xiumin Wu (PLoS ONE, 2025)
This study investigates how Internet embeddedness moderates the relationship between farmers’ income and perceived social fairness in rural China through the integrated lens of social comparison and relative deprivation theories. Analyzing 1,036 rural households in Sichuan Province via Oprobit regression with instrumental variables, we find that while absolute income growth positively affects PSF, Internet usage significantly weakens this relationship through three mechanisms: (1) expanded reference groups that facilitate upward social comparisons, (2) algorithmic distortion of economic reality through selective content exposure, and (3) cognitive overload from excessive income-related information. These findings reconcile conflicting evidence in the income-fairness literature by demonstrating how digital connectivity transforms traditional comparison processes. This study contributes to development economics by highlighting the dual role of technology in rural welfare, while enabling information access, it may inadvertently undermine fairness perceptions through psychological and algorithmic channels. The policy implications suggest the need to complement income growth strategies with digital literacy programs and platform governance to mitigate comparison biases.